Insecticidal effects of the pandanus (Pandanus amaryllifolius Roxb. ex Lindl.; Pandanaceae) leaf powder against rice weevil (Sitophilus oryzae Linnaeus 1753; Curculionidae) - Oviana Lisa; Sumeinika Fitria Lizmah; Putri Mustika Sari; Mustaqim Mustaqim (LPPM Universitas Negeri Jakarta, 2024)
The reduction in the quantity and quality of food can occur during storage in warehouses due to the infestation of rice weevils (Sitophilus oryzae). Environmentally friendly control methods for rice weevil pests are needed, such as using botanical insecticides made from fragrant pandan leaf powder. This research aimed to determine the effects of fragrant pandan leaf powder insecticide on rice weevil pests. The research design used was a non-factorial Completely Randomized Design (CRD) utilizing four dosage levels: 15, 30, 45, and 60 g. The results showed that the dosages had a significant effect on rice weevil mortality, with the highest mortality rate found at the 60 g dosage, reaching 43.50%. The implications of the findings indicated that while higher doses of fragrant pandan leaf powder (60 g) significantly increase rice weevil mortality and also lead to rice weight loss, a balanced dose of bio-insecticide is needed to avoid excessive damage to the rice. Additionally, the organoleptic test results indicate that lower doses (15 g and 30 g) are more preferred by consumers for color, taste, and aroma, which implies that careful dosage control is crucial for both pest control effectiveness and maintaining consumer acceptance.